Combined long nerve allograft and nerve transfer for functional recovery of ulnar nerve: case study with longitudinal clinical and neurodiagnostic follow-up - Cushman, Caroline; Arunachalam Sakthiyendran, Naveen; Hernandez, Evan J.; Kurtzke, Robert N.; MacKay, Brendan J. (Frontiers in Neuroscience, 2025)
BackgroundPeripheral nerve injuries involving large gaps (>50 mm) are associated with poor outcomes due to delayed axonal regeneration and limited reconstructive options. While autografts are traditionally the gold standard, their use is limited by donor site morbidity and length constraints. Processed nerve allografts have emerged as an alternative, but data on their long-term efficacy, particularly for gaps ≥60 mm remain limited.Case reportWe present a case of a 15-year-old male with a 68-mm ulnar nerve gap following trauma reconstructed acutely with a processed nerve allograft. This procedure was performed in conjunction with an anterior interosseous nerve (AIN) to ulnar motor branch transfer and ulnar nerve decompression of potential entrapment sites.ResultsSerial assessments over 4.5 years demonstrated substantial recovery. By 16 months, the patient had regained strong grip strength, full range of motion, and near-normal sensory thresholds. At final follow-up, he had returned to all activities without limitations. Serial EMGs confirmed early nascent motor unit recruitment by 3 months, progressive reinnervation at 16 months, and persistent low-amplitude responses at 54 months, suggestive of ongoing but incomplete reinnervation.ConclusionThis case provides the longest known electrodiagnostic follow-up of a long-gap ulnar nerve allograft reconstruction. It supports the feasibility of processed allografts for gaps ≤70 mm and emphasizes the value of long-term EMG monitoring in tracking regeneration. These findings contribute critical data to a sparsely studied domain and help define expectations for complex nerve repairs.